PENGARUH PEMBERIAN KOMPOS SERASAH DAUN KAKAO TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Lisbet Melisa Panjaitan; Tengku Nurhidayah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The perpose of this research is to find the effect of cocoa leaf compost on the growth of cocoa seedlings and get dosage the best cocoa leaf compost for cocoa seedling growth (Theobroma cacao L.). This research was conducted in Experimental Garden of Agriculture Faculty of Universitas Riau, Bina Widya Campus, Simpang Baru Village, Tampan Sub District, Pekanbaru. This research was conducted for 4 months starting from October to February 2018. The experiment was conducted experimentally using Completely Randomized Design (RAL).Consisting of 6 treatments: K0 (without compost), K1 (50 g), K2 (100 g), K3 (150 g), K4 (200 g), and K5 (250 g) cocoa leaf litter compost. Parameter observed are high seedling,stem diameter,number of leaf,canopy dry weight,root dry weight and root canopy ratio.The data obtained were analyzed statistically using Analysis of Variance (ANOVA) and continued with Duncans New Multiple Range Test (DNMRT) at 5% level.the results showed that the giving of cocoa leaf litter gave a real effect on the growth of heigh seedling, stem diameter, number of leaf, however give out influence is not real to canopy dry weight androot dry weight. Provision of 150-250 g/polybag cocoa leaf compostpolybags show the highest average of each observation parameter and provide the best growth. Keywords: cocoa, compost, cocoa leaf